Strength prediction and failure mode classification for SRC shear beams using GA-BP ANN method - Gangfeng Yao; Bingyi Li (Case Studies in Construction Materials)
For the steel reinforced concrete (SRC) beam, accurately predicting its shear behavior can be quite challenging. Considering the advantages of machine-learning (ML) approaches, the back-propagation (BP) artificial neural network (ANN) method combined with genetic algorithm (GA) was employed to the prediction of strength and failure mode of SRC shear beams. The parameters considered in this study are shear span-to-effective depth ratio, axial concrete compressive strength, ratio of stirrup area, ratio of steel-web area, tension rebar ratio, yield strengths of various steels and a coefficient introduced to consider the concrete-confined effect. To gain the best ANN model, the optimum input combination, hidden-nodes number, weights and biases were firstly researched and determined, based on a newly-built database of 130 experimental specimens. Then, the importance of input variables were analyzed and the most recommended models were provided. Finally, a comparative study was also conducted between the ANN models and literature methods. Results indicate that the shear span-to-effective depth ratio, axial concrete compressive strength and ratio of steel-web area are the three most important variables to shear strength. As for the failure mode, the shear span-to-effective depth ratio is the most influential factor. Besides, the coefficient account for concrete-confined effect enhances the predictive accuracies of ANN models for shear capacity. Compared to the literature methods, the ANN models show a much better performance both in predicting shear strength and failure mode.